Dampak Perilaku Masyarakat terhadap Pilihan Penggunaan Lahan pada Daerah Aliran Sungai - Pambudi, Andi Setyo; Bambang Pramujo (CV. Creative Tugu Pena, 2024)
Watershed (DAS) Management cannot be separated from the ecosystem's behavior in it. The interaction in upstream Brantas watershed ecosystems is highlighted when various studies have shown that the rate of erosion in this area over the last 15 years has continuously increased. The population growth that increases land use affects the current erosion rate. The population factor in the upper Brantas watershed concerning erosion is influenced by the people's knowledge, attitudes, and behavior. The Lesti sub-watershed as the upstream area of the Brantas watershed is a suitable study location to be analyzed to determine the relationship between behavior and erosion through land-use choices in this area. The condition of the Lesti sub-watershed impacts the Sengguruh Reservoir in Malang Regency, which supplies water for electricity, agriculture, and other water needs in East Java. This study aims to determine the relationship between community behavior and land use choices at the sub-watershed scale, which will be helpful to decide on priority policy recommendations in this region in the future. The method used in the analysis is a mixed-method through literature studies and statistical analysis based on a sample of community respondents in 12 sub-districts in the Lesti sub-watershed area. The analysis results show that there is a relationship between land use and community behavior that affects the rate of erosion. Environmental education and limited population relocation are suggested as priority policies in this region to support social aspects in managing the Brantas watershed.